Application of geoinformation technologies for the assessment of landscape structure using landscapeecological indexes (case study of the Handlová landslide) - Oláhová, Jana; Vojtek , Mataj; Boltižiar, Martin (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
New versions of geoinformation technologies and its various extensions enable to obtain quality and more accurate information about the landscape and its properties. The aim of the paper is to point out to the use of selected extensions in geographic information systems (GIS) which make the time-consuming and complex calculations within the analysis, assessment and interpretation of the landscape more effective. With the use of digital vector map, it is possible, by the means of GIS extensions, to calculate the number, shape, size, dispersion, diversity, neighboring relations of patches as well as many other indexes. In the paper, we deal with three extensions (V-LATE, Patch Analyst, and StraKa) that are compatible with ArcGIS/ArcView software. These specialized extensions were applied for the analysis of the spatial landscape structure in the area of the catastrophic Handlová landslide from the year 1961 which was analyzed also in terms of changes in landscape structure for the time period of 228 years.